From Laughter to Learning: Using Humor in Contextual Teaching to Foster Engagement in College Students - Qudsyi, Hazhira; Ahmad Rusdi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to explore the integration of humor into the Contextual Teaching and Learning (CTL) approach as a learner-centered strategy to support student engagement in higher education. A quasi-experimental one-group pretest–posttest design was employed with 47 undergraduate psychology students enrolled in a Positive Psychology in Schools course. Humor was integrated into CTL through learning materials, assignment instructions, discussions, quizzes, self-reflection activities, and group activities, serving to attract attention, support recall, provide feedback, and create opportunities for humorous breaks. Student engagement and sense of humor were measured before and after the intervention. The data were analyzed using repeated-measures ANOVA. The results indicated significant increases in student engagement (p = 0.015, η²p = 0.122) and sense of humor (p = 0.032, η²p = 0.096) from pretest to posttest. These findings suggest the potential value of integrating humor into CTL as a learner-centered pedagogical practice. The study extends previous research on instructional humor by examining its integration within a contextual learning approach rather than treating humor solely as a teacher-delivered instructional technique. However, the absence of a control group and the context-specific focus on a single course limit causal interpretations and the generalizability of the findings. Future research should examine different forms and mechanisms of learner-centered humor using controlled designs and larger, more diverse samples.